An overview of the medical-physics-related verification system for radiotherapy multicenter clinical trials by the Medical Physics Working Group in the Japan Clinical Oncology Group–Radiation Therapy Study Group. (29th September 2020) - Nishio, Teiji; Nakamura, Mitsuhiro; Okamoto, Hiroyuki; Kito, Satoshi; Minemura, Toshiyuki; Ozawa, Shuichi; Kumazaki, Yu; Ishikawa, Masayori; Tohyama, Naoki; Kurooka, Masahiko; Nakashima, Takeo; Shimizu, Hidetoshi; et al.
Abstract: The Japan Clinical Oncology Group – Radiation Therapy Study Group (JCOG-RTSG) has initiated several multicenter clinical trials for high-precision radiotherapy, which are presently ongoing. When conducting multi-center clinical trials, a large difference in physical quantities, such as the absolute doses to the target and the organ at risk, as well as the irradiation localization accuracy, affects the treatment outcome. Therefore, the differences in the various physical quantities used in different institutions must be within an acceptable range for conducting multicenter clinical trials, and this must be verified with medical physics consideration. In 2011, Japan's first Medical Physics Working Group (MPWG) in the JCOG-RTSG was established to perform this medical-physics-related verification for multicenter clinical trials. We have developed an auditing method to verify the accuracy of the absolute dose and the irradiation localization. Subsequently, we credentialed the participating institutions in the JCOG multicenter clinical trials that were using stereotactic body radiotherapy (SBRT) for lungs, intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) for several disease sites, and proton beam therapy (PT) for the liver. From the verification results, accuracies of the absolute dose and the irradiation localization among the participating institutions of the multicenter clinical trial were assured, and the JCOG clinical trials could be initiated.